The Use of Pawned Goods by Third Parties in the Perspective of Fiqh Muamalah (Case Study in Gejiwan Village, Krasak, Salaman District, Magelang Regency, Central Java) - Aurora Asyabig Azka Attral; Ahmad Misbakh Zainul Musthofa; Rizki Dwi Anggraini (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the practice of using motorcycle collateral by third parties in rahn contracts without rahin approval in Gejiwan Village, Krasak, Salaman District, Magelang Regency, Central Java. Using an empirical juridical approach with qualitative methods through interviews, observations, and documentation of four informants. The findings of the study revealed that motor vehicles that were used as collateral were transferred to a third party without the consent of rahin as the legal owner. This transfer does not meet the legal requirements of rahn in fiqh muamalah because of the absence of the owner's permission and the clarity of the contract between the parties. In addition, the profits received by murtahin through the handover of third-party funds clearly resemble the practice of usury which is prohibited in Islamic law. Although it is based on the spirit of ta'awun, the practice needs to be reviewed to be in harmony with the principles of fiqh muamalah. Keywords: Rahn, Pawn Goods, Third Party, Fiqh Muamalah